2014
DOI: 10.1007/s12178-014-9228-9
|View full text |Cite
|
Sign up to set email alerts
|

Updates in biological therapies for knee injuries: anterior cruciate ligament

Abstract: There have been many advances in anterior cruciate ligament reconstruction (ACLR) techniques incorporating biological treatment. The aim of this review is to discuss the recent contributions that may enlighten our understanding of biological therapies for anterior cruciate ligament (ACL) injuries and improve management decisions involving these enhancement options. Three main biological procedures will be analyzed: bio-enhanced ACL repair, bio-enhanced ACLR scrutinized under the four basic principles of tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 66 publications
0
28
0
7
Order By: Relevance
“…Unlike the comparison using only BPTB grafts for intraarticular reconstruction in combined and isolated ACL reconstruction groups, analysis of procedures using only hamstring grafts showed that a substantially greater proportion of patients who underwent combined reconstruction achieved normal or nearly normal Lachman test results and side-toside differences less than 3 mm on KT-1000 arthrometer testing. Results of our subgroup analyses of superior stability of BPTB grafts compared with hamstring grafts may be related to the delayed ligamentization of hamstring tendons as opposed to BPTB grafts [7,11,31]. As a result, the hamstring graft may be more disposed to deformation and elongation during ligamentization, which may be prevented by the addition of an extraarticular procedure [32].…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the comparison using only BPTB grafts for intraarticular reconstruction in combined and isolated ACL reconstruction groups, analysis of procedures using only hamstring grafts showed that a substantially greater proportion of patients who underwent combined reconstruction achieved normal or nearly normal Lachman test results and side-toside differences less than 3 mm on KT-1000 arthrometer testing. Results of our subgroup analyses of superior stability of BPTB grafts compared with hamstring grafts may be related to the delayed ligamentization of hamstring tendons as opposed to BPTB grafts [7,11,31]. As a result, the hamstring graft may be more disposed to deformation and elongation during ligamentization, which may be prevented by the addition of an extraarticular procedure [32].…”
Section: Discussionmentioning
confidence: 99%
“…Na análise de subgrupos avaliando apenas os indivíduos praticantes de futebol, não houve diferença na taxa de retorno ao esporte apesar do fundamento teórico da associação sinérgica entre reabilitação acelerada pós-reconstrução do LCA e preservação do remanescente já reportado em estudos prévios. 7,8,12,13 Um dos fatores que parecem otimizar a reabilitação nesses indivíduos com preservação do remanescente está relacionado à proteção mecânica ao enxerto promovida pelo coto do remanescente no pós-operatório precoce, não dependendo somente dos dispositivos de fixação na fase inicial de incorporação do enxerto. 7,8,13 Além disso, a inervação proprioceptiva também potencializaria o retorno ao esporte, já que os indivíduos com fibras do remanescente intactas parecem apresentar maior senso de posição da articulação (joint position sense), o que se traduz em maior controle do membro na retomada da prática esportiva com pivoting.…”
Section: Discussionunclassified
“…7,8,12,13 Um dos fatores que parecem otimizar a reabilitação nesses indivíduos com preservação do remanescente está relacionado à proteção mecânica ao enxerto promovida pelo coto do remanescente no pós-operatório precoce, não dependendo somente dos dispositivos de fixação na fase inicial de incorporação do enxerto. 7,8,13 Além disso, a inervação proprioceptiva também potencializaria o retorno ao esporte, já que os indivíduos com fibras do remanescente intactas parecem apresentar maior senso de posição da articulação (joint position sense), o que se traduz em maior controle do membro na retomada da prática esportiva com pivoting. 7,8,13 Entretanto, no presente estudo, não foi possível confirmar essa superioridade teórica do grupo com preservação do remanescente na avaliação do desfecho retorno ao esporte, o que torna necessária a realização de mais estudos clínicos com melhor refinamento metodológico para apurar tais achados.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…These findings can be applied to recently described remnant preservation ACL reconstruction techniques. 8,16,19 …”
Section: Discussionmentioning
confidence: 99%